Relationship between growth hormone deficiency and nonalcoholic fatty liver disease in patients with pituitary stalk interruption syndrome. (17th April 2022) - Huang, Qibin; Xu, Hongli; Wang, Xi; Mao, Jiangfeng; Yu, Bingqing; Zhu, Yiyi; Zhang, Rui; Sun, Bang; Zhang, Junyi; Ji, Wen; Ma, Wanlu; Nie, Min; et al.
Abstract: Background: Pituitary stalk interruption syndrome (PSIS), characterized by thinning or disappearance of the pituitary stalk, hypoplasia of the anterior pituitary, and an ectopic posterior pituitary, can lead to congenital combined pituitary hormone deficiency. There is a high prevalence of various metabolic disorders, including nonalcoholic fatty liver disease (NAFLD), in this population. Objective: To investigate the characteristics of NAFLD in Chinese adult patients with PSIS and its association with growth hormone deficiency. Design: Retrospective cross‐sectional study in a tertiary referral center of China. Patients: Adult patients with PSIS diagnosed, followed up between September 2019 and August 2021, were consecutively enrolled. Measurements: Abdominal ultrasonography images were evaluated and noninvasive fibrosis scores were determined to assess the severity of NAFLD. Anthropometric, clinical, and biochemical parameters were compared between patients with and without NAFLD. Logistic regression was performed to assess the independent effects of insulin‐like growth factor‐1 (IGF‐1) on NAFLD. Results: A total of 93 patients (77 men, 16 women, mean age: 29.6 ± 7.1 years) were included. The prevalence of NAFLD and advanced fibrosis/cirrhosis was 50.5% and 4.3%, respectively. Insufficient hormone therapy and prominent metabolic disorders, including central obesity, dyslipidemia, insulin resistance, and metabolic syndrome, were more common in the NAFLD (+) group. After adjusting for multiple variables, IGF‐1 <−2 standard deviation score (SDS) was found to be associated with an increased prevalence of NAFLD (odds ratio [OR]: 4.92, 95% confidence interval [CI]: 1.21–24.55, p = .035). Per 1 SDS increase in IGF‐1 was associated with a 27% lower risk of NAFLD (OR: 0.73, 95% CI: 0.52–0.97, p = .042). Conclusion: NAFLD is a frequent comorbidity among Chinese adult patients with PSIS and is strongly associated with lower IGF‐1 levels. Timely and appropriate hormone replacement, particularly growth hormone may contribute to decreasing the risk of NAFLD in these patients.